Frequency and Risk factors of Low Birth Weight in Rawalpindi, Pakistan - Usman Zafar, Sadia Zafar, Nadia Tariq, Farah Rashid, Khalid Hassan (Journal of Rawalpindi Medical College, 2021)
Background: Low birth weight is a key determinant of infant survival, health and development. There are many maternal and biological risk factors for it. The objective of this study is to determine frequency and associated risk factors of Low birth weight. Methods: This cross-sectional study was carried out in department of obstetrics and gynecology; al Razi hospital, Rawalpindi from June 2016 till June 2020. Total sample size was 20,681 which was the total births during these years in this hospital setting. A structured pre tested questionnaire was used for data collection. SPSS version 23 was used for data analysis. Frequencies and percentages were calculated. Chi square test was used to determine association between LBW and socio demographic variables Result: The overall frequency of LBW was found to be 8.9%. Female babies were more likely to have LBW as compared to male babies (p=0.000). LBW babies had poor APGAR scoring as compared to normal weight (p=0.000). The frequency of LBW was higher amongst the mother who were <20years of age and >30years. Maternal weight had a direct while parity had inverse relationship with LBW. Conclusion: Low birth weight babies have poor APGAR scoring and associated with maternal risk factors.